Exploring cultures of doctoral supervision: Narrative perspectives from the International Islamic University Malaysia - Sahar, Rafidah (2017)
My study sought to understand the experiences of doctoral supervision as narrated to me by some doctoral graduates and experienced supervisors from a public university in Malaysia. As stimulated through face-to-face, one-to-one encounters, in English and/or Bahasa Malaysia, I generated narratives of supervisory experiences from six graduates and three supervisors. These narratives were then restoried in English and analysed using holistic-content approach (Lieblich et al., 1998) to reveal the global impression and key themes of supervisory experiences of the individual participants. Findings from the narrative analysis were interpreted through the non-essentialist small cultures theoretical lens (Holliday, 1999). From the interpretation, I proposed that the emerging small cultures of doctoral supervision are characterised by the following features: the students’ learning process; the supervisory styles; the supervisory roles; the supervisory relationships; and the expectation of students and supervisors.